2018
DOI: 10.5455/javar.2018.e292
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological interpretations on the bones of the pelvic limb of New Zealand rabbit (Oryctolagus cuniculus) and domestic cat (Felis domestica)

Abstract: Objective: Regarding the displaying of the main differences between the pelvic limb of rabbit and cat. Materials and methods: Our work was performed on 10 New Zealand rabbits ( Oryctolagus cuniculus ) and domestic cats ( Felis domestica ) with variable ages and of both sexes. After weighing of the animals, sedation, and anesthesia, the animals were examined radiographically. The bones of the pelvic limb were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 5 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…The division of the number of tendons to the fingers is related to the degree of movement of the digits. 23 These muscular characteristics are consistent with the behavior of each species during the hunting of its prey, 24 both in the distances they travel and in the size of the different preys.…”
Section: Discussionsupporting
confidence: 55%
“…The division of the number of tendons to the fingers is related to the degree of movement of the digits. 23 These muscular characteristics are consistent with the behavior of each species during the hunting of its prey, 24 both in the distances they travel and in the size of the different preys.…”
Section: Discussionsupporting
confidence: 55%
“…Conversion to craniocaudal loading eliminated this as supports were now balanced on the flatter caudal surface. 33,35 This methodology has been corroborated by other femoral defect model experiments, where anteroposterior deficits 15 and three-point bending 36,37 were used for biomechanical evaluation. Fourpoint bending is an alternative to minimize shear-however, boundary constraint errors may still result from the short femoral span length.…”
Section: Discussionmentioning
confidence: 79%
“…32 With feline femoral diaphysis not uniformly tubular, the shear component of three-point bending was accentuated with mediolateral HB during pilot trials. 33,34 Resultant indiscriminate rotations led to sizable variations and was not reflective of pure bending to be evaluated. Conversion to craniocaudal loading eliminated this as supports were now balanced on the flatter caudal surface.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these measurements hold an important place in determining morphological variations and taxonomic classifications among different species of the same genus; as well as identifying the differences between sexes [5,23,38]. For this purpose, many studies have been conducted on humans [21,22,42] and animals [2,5,9,10,16,14,29,33,36] that involved obtaining osteometric measurements on the long bones of their pelvic limbs. In our study, the morphometric, volumetric and surface area measurements of the femur, tibia, and fibula of adult Van cats were obtained via CT scans and 3D modeling, in order to identify the differences between the two sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have been performed to determine the anatomical and osteometrical properties of the main long bones of the pelvic limbs (femur, tibia, fibula) of different animal species, like mole-rats (Spalax leucodon Nordmann) [34], African giant rats (Cricetomys gambianus Waterhouse) [27], grasscutter rodents (Thryonomys swinderianus, Temminck-1827) [29], guinea pigs (Cavia porcellus) [37], feral pigs (Sus scrofa) [19], martens (Martes fonia) [3], badgers (Meles meles) [32], squirrels (Sciurus vulgaris) [31], hedgehogs hedgehog (Erinaceus europaeus L.) [35], porcupines (Hystrix Cristata) [49], chinchillas (Chinchilla lanigera) [10], lumholtz tree-kangaroo (Dendrolagus lumholtzii) [40], Anatolian bobcats (Lynx lynx) [30], New Zealand rabbits (Oryctolagus cuniculus) [1,16,36], marmosets (Callithrix jacchus) [9], brown bears (Ursus arctos) [13], deers (Hippocamelus bisulcus) [41], sheeps (Ovis aries) [2], gazelles (Gazella subgutturosa) [12], foxes (Vulpes vulpes and Alopex lagopus) [24], dogs (Canis lupus familiaris) [28,43], and domestic cats (Felis catus and Felis domestica) [5,16]. No study was found when the existing literature was searched for long bones of the pelvic limbs of Van cats, however.…”
Section: Introductionmentioning
confidence: 99%